The use of recombinant hemagglutinine protein of rinderpest virus in enzyme immunoassay - Bulut, H; Bolat, Y; Bulut, Y; Özdarendeli, A; Doymaz, MZ (Tubitak Scientific & Technological Research Council Turkey, 2003)
In this study, Rinderpest virus (RPV) recombinant hemagglutinine protein (rH) fused with protein A region of Staphylococcus aureus was expressed in Escherichia coli and purified by IgG affinity chromatography. rH protein was also used to establish enzyme immunoassay. Therefore, to prevent IgG binding to the protein A the wells coated with the rH proteins were blocked by human serum. Afterwards, RPV antigens were added to the wells to evaluate this assay. To this end, serum from mice immunized with RPV was used for EIA. Our data indicated that the rH protein fused with protein A of Staphylococcus aureus can be reliably used for enzyme immunoassays.
Si?ir vebasi virüsü rekombinant hemaglutinin proteininin enzim i?mmunoassayda kullanimi
Keywords: Rinderpest virus; recombinant hemagglutinine protein; enzyme immunoassay